The Relationship of Self-Regulation and Career Planning: A Study of Senior High School Students - Sofyan Abdi; Sulistiasih Sulistiasih; Dwi Endrasto Wibowo; Ivo Imani Cantika; Elsa Violita (Kuras Institute, 2023)
This research aims to determine whether there is a relationship between self-regulation and career planning among twelfth-grade students at SMAN 100 East Jakarta. This study was conducted using a quantitative approach, specifically a correlational research design. The population of this study consisted of all twelfth-grade students at SMAN 100 East Jakarta, totaling 235 students. Sample calculation using the Slovin formula resulted in a sample of 148 students using simple random sampling technique. Data collection employed psychological scales for self-efficacy, self-regulation, and career planning. Data analysis technique involved simple linear regression analysis, followed by classical assumption tests including normality test, multicollinearity test, and heteroskedasticity test. The research instruments utilized psychological scales for self-regulation and career planning. The results of the study indicate a positive and significant relationship between self-regulation and career planning, with a significant value of 0.000 and an F value of 99.409. Therefore, since the significance value is less than 0.05 and the F value is greater than the F table value (3.06), the null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted. Based on the coefficient of determination, the obtained R Square value of 0.578 indicates that self-regulation influences career planning by 57.8%, while the remaining 42.2% is influenced by other factors.